2020
DOI: 10.3389/fmed.2020.00466
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib Rapidly Reduces Acute Respiratory Distress Syndrome in COVID-19 Disease. Analysis of Data Collection From RESPIRE Protocol

Abstract: spontaneous breathing), 4/18 patients had minimal oxygen requirement (2-4 L/m), 1/18 patient showed stable disease, and 2/18 patient showed progressive disease. After 14 days, 16/18 patients showed complete recovery of respiratory function (ORR 89%). Compliance to ruxolitinib planned treatment was 100% and no serious adverse event was recorded. In our case series of 18 critically ill patients with COVID-19 and ARDS, administration of ruxolitinib resulted in a clinical improvement that concurred to modify the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 23 publications
2
57
0
1
Order By: Relevance
“…Other three single arm not randomized studies were published so far about the use of Ruxolitinib in Covid-19 . All confirm a fast effect of the drug reducing markers on infection and improving signs of respiratory distress [21][22][23] The important role of lung hyperinflammation in Covid-19 19 is again supported by the present study.…”
Section: Accepted Articlesupporting
confidence: 85%
“…Other three single arm not randomized studies were published so far about the use of Ruxolitinib in Covid-19 . All confirm a fast effect of the drug reducing markers on infection and improving signs of respiratory distress [21][22][23] The important role of lung hyperinflammation in Covid-19 19 is again supported by the present study.…”
Section: Accepted Articlesupporting
confidence: 85%
“…Ruxolitinib induced inhibition of the IL-6/JAK/STAT3 pathway could cause a significant reduction of IL-6 levels [ 98 ]. It can overcome complications due to immune hyperactivation by the JAK/STAT signal transduction pathway and potentially knockdown the hyper inflammation reducing the lung impairment and restoring the PaO2/FiO2 ratio in COVID-19 patients [ 99 ].…”
Section: Jak/stat Inhibitors As Therapeutic Agents Against Covid-19mentioning
confidence: 99%
“…On the bases of all biological premises ( 62 , 115 , 118 129 ), and of our preliminary results, we firmly believe that ruxolitinib presents a strong potential in overcoming lung and systemic complications caused by JAK/STAT-mediated immune hyperactivation during COVID-19 disease. Indeed, while recent works in this field ( 123 125 , 127 ) demonstrated a promising activity of ruxolitinib in avoiding respiratory worsening and progression to mechanical ventilation in hyperinflamed patients at imminent risk to be admitted to ICU (by using different treatment schedules, including a dose escalation in case of not-responding patients), here we presented a case-report documenting the potential activity of the drug (with a slightly different 20-days schedule which include a preplanned dose intensification followed by a decalage phase) in patients already under mechanical ventilation, thus extending the possibility of using this drug in critical patients (our patient was indeed quickly intubated after treatment beginning and received ruxolitinib through a nasogastric tube). Anyway, while using different timings and schedules, all the studies reported a clinical benefit within few days from treatment starts without major signs of ruxolitinib-associated toxicities (mainly due to the short treatment courses) underscoring the need of larger studies (phase 3 studies are ongoing) to confirm the activity of the drug in hyperinflamed COVID-19 patients regardless of the respiratory support they need.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, while using different timings and schedules, all the studies reported a clinical benefit within few days from treatment starts without major signs of ruxolitinib-associated toxicities (mainly due to the short treatment courses) underscoring the need of larger studies (phase 3 studies are ongoing) to confirm the activity of the drug in hyperinflamed COVID-19 patients regardless of the respiratory support they need. Ruxolitinib-related side effects, when present, could be managed and resolved through a fruitful and humble cooperation between oncohematologists familiar to the drug ( 130 133 ) and clinicians from infectious disease, lung and intensive care units ( 118 , 123 125 , 127 , 130 , 134 ), without being misled by false convictions, lack of personal experience, overestimated toxicity ( 134 ) or by unethical conflicts of interests. In line with what recently highlighted in Lancet ( 135 ) and by La Rosée and colleagues ( 127 ), in this sad and difficult historical moment, patients deserve the best possible care and kind evaluation of new agents, communicating positive results immediately and promptly to the whole scientific community and translating new observational findings into structured (randomized) and methodologically correct clinical trials.…”
Section: Discussionmentioning
confidence: 99%